#TITLE_ALTERNATIVE# - (NIM 15304087), KARLINA
Citarum River is one of river that lies at West Java that is used for many purposes for human wealth. As time goes by the growth of industry and population has increased industrial and domestic waste load in Citarum River and has caused pollution at Citarum River. The domestic waste that highly contributed to river pollution is garbage. This caused water flow at river become blocked and resulted flood. The highly contributed pollutant from industrial waste is hazardous waste that directly discarded to the river without any treatment. On the other side, the government issued certain policies for dredging Citarum River for anticipating flood which is caused by river level declining. Actually, these policies raise other problem that is sediment piled along river side with greater volume each day. This sediment is one of this experiment focus because it is used by people to plant many crop. And later on this crop is consumed by people who lived along riverside. From the experiment can be known that the plants contained heavy metal such as copper with concentration in the range 5,10-8,00 mg/kg for kangkung and 5,38-9,00 mg/kg for spinach. Cadmium was found in the range of concentration 0,08-1,78 mg/kg for kangkung and 0,10-2,29 mg/kg for spinach. And chromium in concentration 1,05-3,99 mg/kg for kangkung and 1,36-5,19 mg/kg for spinach. It is concluded by correlation analysis that heavy metals that is contained in plants can be higher that it was in sediment that is used as planting media.